Cell cycle and cell-fate determination in Drosophila neural cell lineages. - Fichelson, P.; Audibert, A.; Simon, F.; Gho, M. (Trends in Genetics, 2005)
"Normal" development requires a finely tuned equilibrium between cell differentiation and cell proliferation. Important issues in development include whether the cell cycle controls the cell-fate determination and whether cell identity in turn regulates cell-cycle progression. Although, these issues are of general biological relevance, stereotyped Drosophila neural lineages are particularly suited to address these questions and have provided insights into the links between cell-cycle progression and cell-fate specification.